Introduction to matrics and linear transformations - Finkbeiner, Daniel T. (Delhi CBS publishers & distributors, 1986)
This versatile undergraduate text can be used in a variety of courses in linear algebra. It contains enough material for a two-semester course, and it also serves as a support text and reference. Chapter Ten, on linear programming, will be of special interest to students of business and economics. A balanced combination of formal theory and related computational techniques, this treatment begins with the familiar problem of solving a system of linear equations.
Keywords: Lineare Algebra; Lineare transformation; Mathematics